ARTEMISININ BIOSYNTHESIS PROMOTING KINASE 1 positively regulates artemisinin biosynthesis through phosphorylating AabZIP1. (28th December 2017) - Zhang, Fangyuan; Xiang, Lien; Yu, Qin; Zhang, Haoxing; Zhang, Taixin; Zeng, Junlan; Geng, Chen; Li, Ling; Fu, Xueqing; Shen, Qian; Yang, Chunxian; Lan, Xiaozhong; et al.
Abstract : An ABA-responsive SnRK2-type kinase, AaAPK1, is involved in positively regulating artemisinin biosynthesis in Artemisia annua through phosphorylation of AabZIP1. abstract: The plant Artemisia annua produces the anti-malarial compound artemisinin. Although the transcriptional regulation of artemisinin biosynthesis has been extensively studied, its post-translational regulatory mechanisms, especially that of protein phosphorylation, remain unknown. Here, we report that an ABA-responsive kinase (AaAPK1), a member of the SnRK2 family, is involved in regulating artemisinin biosynthesis. The physical interaction of AaAPK1 with AabZIP1 was confirmed by multiple assays, including yeast two-hybrid, bimolecular fluorescence complementation, and pull-down. AaAPK1, mainly expressed in flower buds and leaves, could be induced by ABA, drought, and NaCl treatments. Phos-tag mobility shift assays indicated that AaAPK1 phosphorylated both itself and AabZIP1. As a result, the phosphorylated AaAPK1 significantly enhanced the transactivational activity of AabZIP1 on the artemisinin biosynthesis genes. Substituting the Ser 37 with Ala 37 of AabZIP1 significantly suppressed its phosphorylation, which inhibited the transactivational activity of AabZIP1. Consistent overexpression of AaAPK1 significantly increased the production of artemisinin, as well as the expression levels of the artemisinin biosynthesis genes. Our study opens a window into the regulatory network underlying artemisinin biosynthesis at the post-translational level. Importantly, and for the first time, we provide evidence for why the kinase gene AaAPK1 is a key candidate for the metabolic engineering of artemisinin biosynthesis.